Tight junction protein claudin‐1 is downregulated by TGF‐β1 via MEK signaling in benign prostatic epithelial cells. Issue 14 (21st July 2020) - Wang, Ke; Pascal, Laura E.; Li, Feng; Chen, Wei; Dhir, Rajiv; Balasubramani, Goundappa K.; DeFranco, Donald B.; Yoshimura, Naoki; He, Dalin; Wang, Zhou
Abstract: Background: Benign prostatic hyperplasia (BPH) is arguably the most common disease in aging men. Although the etiology is not well understood, chronic prostatic inflammation is thought to play an important role in BPH initiation and progression. Our recent studies suggest that the prostatic epithelial barrier is compromised in glandular BPH tissues. The proinflammatory cytokine transforming growth factor beta 1 (TGF‐β1) impacts tight junction formation, enhances epithelial barrier permeability, and suppresses claudin‐1 messenger RNA expression in prostatic epithelial cells. However, the role of claudin‐1 in the prostatic epithelial barrier and its regulation by TGF‐β1 in prostatic epithelial cells are not clear. Methods: The expression of claudin‐1 was analyzed in 22 clinical BPH specimens by immunohistochemistry. Human benign prostate epithelial cell lines BPH‐1 and BHPrE1 were treated with TGF‐β1 and transfected with small interfering RNAs specific to claudin‐1. Epithelial monolayer permeability changes in the treated cells were measured using trans‐epithelial electrical resistance (TEER). The expression of claudin‐1, E‐cadherin, N‐cadherin, snail, slug, and activation of mitogen‐activated proteins kinases (MAPKs) and AKT was assessed following TGF‐β1 treatment using Western blot analysis. Results: Claudin‐1 expression was decreased in glandular BPH tissue compared with adjacent normal prostatic tissue in patient specimens. TGF‐β1 treatment or claudin‐1 knockdown in prostatic epithelial cell lines increased monolayer permeability. TGF‐β1 decreased levels of claudin‐1 and increased levels of snail and slug as well as increased phosphorylation of the MAPK extracellular signal‐regulated kinase‐1/2 (ERK‐1/2) in both BPH‐1 and BHPrE1 cells. Overexpression of snail or slug had no effect on claudin‐1 expression. In contrast, PD98059 and U0126, inhibitors of the upstream activator of ERK‐1/2 (ie, MEK‐1/2) restored claudin‐1 expression level as well as the epithelial barrier. Conclusion: Our findings suggest that downregulation of claudin‐1 by TGF‐β1 acting through the noncanonical MEK‐1/2/ERK‐1/2 pathway triggers increased prostatic epithelial monolayer permeability in vitro. These findings also suggest that elevated TGF‐β1 may contribute to claudin‐1 downregulation and compromised epithelial barrier in clinical BPH specimens.